2, 2′-Peroxybis(tetrahydrofuran), a tenuously stable but persistent hazardous contaminant of THF: a fortuitous entrapment as co-crystal with a polycyclitol. Issue 48 (30th November 2016) - Rashid, Showkat; Bhat, Bilal A.; Sen, Saikat; Mehta, Goverdhan
Graphical abstract: Highlights: A novel co-crystal I of THF peroxide II with polycyclitol III has been presented. Co-crystal I appears as 'inclusion complex' of II within crystal framework of III. Arrangement of molecules in I follows a sandwich stack like ⋯A⋯B⋯A⋯ pattern. A comparison of crystal structures of I and unsolvated III has been presented. The observations have implications on the wide spread use of THF as solvent. Abstract: Details of isolation and unambiguous structural elucidation of a novel co-crystal of 2, 2′-peroxybis(tetrahydrofuran), generated through an in situ aerial oxidation of the solvent THF, with a polyhydroxy-decalin (polycyclitol) are delineated, and may have implications on the wide spread use of this solvent.